Double-orifice mitral valve associated with atrioventricular canal defects - Rhissassi, Jaafar (Pan Afr Med J, 2016)
A 4 year-old male presented with effort dyspnea, and was diagnosed as atrioventricular canal defects. This finding was confirmed by open heart surgery, and a congenital double orifice mitral valve was discovered. The septal defect was closed but the double orifice mitral valve was respected because of the absence of hemodynamic disturbance. We report this case with review of literature.